Bentuk dan Pola Kemitraan pada Masyarakat Nelayan Cilacap - Harfina S, Dewi; Djohan, Eniarti B. (TINGKAP, 2015)
This article is extracted from the research report looking at the life of fishermen communities in Cilacap, especially in terms of the form and the pattern of partnership among the fishermen communities in Cilacap, West Java. The purpose of the research is firstly observing the life of Cilacap fishermen communities in general; secondly, the paterns of partnership on fishing activities in Cilacap; and thirdly, the implementation of the partnership on fishing activities and its impact on the empowerment of maritime culture Â among the the Cilacap fishermen communities. According to the author, the life of Indonesian fishermen still classified in the group of marginalized people. To improve the livelihood of fishermen, it is required to do the efforts of various parties, particularly in strengthening the capacity of the fishermen. Synergic relationship among stakeholders who have the same goal in fishing activities need to be improved by supporting by the government programmes. The perpetrators of the partnership is also expected to respect each other in developing the potential or planned activities in order to get mutual benefit by way of strengthening the independent relationship and not as a dependency form.Keywords: Partnership, fisheries, fishermen community, synergistic relationship